Crowdsourcing in the Quaternary sea level community: insights from the Pliocene - Rovere, A.; Raymo, M.; O'Leary, Mick; Hearty, P. (Pergamon, 2012)
In order to establish the ‘fingerprint’ of past sea level changes, many field measurements of paleo sea level from globally distributed locations are needed. It is because this problem requires a geographically expansive database that it becomes an ideal candidate for crowdsourcing techniques. In order to crowdsource sea level data from the Mid-Pliocene Warm Period, we developed three tools: PlioWiki, RSLcalc and RSLmap. PlioWiki is a web portal, open to contributions, where investigators can share knowledge on Pliocene to Quaternary relative sea levels. RSLcalc is a standardized, ready-to-use tool for field geologists to log their own sea level field observations and, if they desire, submit new data to an open access database of relative sea level markers. RSLmap allows one to visualize and query the database built with RSLcalc on a Google Map interface. Here we describe these tools and discuss the advantages of crowdsourcing, relative to traditional approaches, for the creation of sea level databases for any time period. Highlights: ► The creation of databases of relative sea level (RSL) markers can be crowd-sourced. ► To achieve this goal, PLIOMAX has created three tools: PlioWiki, RSLcalc and RSLmap. ► The tools can be used to build RSL datasets. ► They will therefore help scientists in creating past sea level ‘fingerprints’.